Achieving systemic delivery of oncolytic viruses - Hill, C; Carlisle, R (Taylor and Francis, 2019)
Introduction: Oncolytic virotherapy is a selective and powerful tool for cancer treatment. Studies proving the ability of oncolytic viruses (OVs) to target and rapidly kill cancer cells have led to approval of H101 and Imlygic®. Both these OVs are restricted to intratumoral administration into cancer lesions. Despite promising preclinical results, systemic delivery of OV has shown limited success in patients due to a knockdown in infectivity, as a result of rapid immune-mediated neutralization, and poor penetration into tumors. Areas covered: This review catalogs the techniques used to enhance OV delivery. Firstly, insights from clinical trials of OV provide evidence of the need for enhanced delivery strategies. Secondly, the techniques applied to overcome the challenges highlighted by clinical trial data (i.e. suboptimal pharmacokinetics, antiviral immune responses, and poor penetration into solid tumors) are reviewed. Expert opinion: For OV to gain traction and convert potential into value, researchers focussed on showing clinical and commercial viability following intratumoral injection. For the technology to mature and become applicable across a wider range of patients/cancer indications, amenability to systemic delivery is required. This may be achieved using strategies that modulate the OV by genetic or chemical means and/or that alter the physiology of target tumors.